2010
DOI: 10.1530/eje-09-0622
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in hyperthyroidism: the role of IL6 and TNFα

Abstract: Objective: Although insulin resistance is a common finding in hyperthyroidism, the implicated mechanisms are obscure. The aim of this study was to investigate whether interleukin 6 (IL6) and tumour necrosis factor a (TNFa) are related to the development of insulin resistance in hyperthyroidism of nonautoimmune origin. Design and methods: A meal was given to ten hyperthyroid (HR) and ten euthyroid (EU) women. Plasma samples were taken for 360 min from the radial artery for measurements of glucose, insulin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 31 publications
(39 reference statements)
2
30
0
7
Order By: Relevance
“…However, we have recently shown that glucose uptake in muscle in HR is indeed resistant to insulin, but this defect is masked by a marked increase in blood flow (4); this could be attributed to the dramatic decrease in intracellular pathways of insulin-stimulated glucose metabolism (such as glycogen synthesis) (25,26). In addition, tumor necrosis factor a and interleukin 6 may contribute to insulin resistance in the metabolism of both lipids and glucose in HR (27). These findings support the results of the present study: in HR patients, glucose uptake in monocytes in the presence of insulin was significantly decreased compared to euthyroid subjects; the SHR group showed an intermediate response suggesting that SHR is an intermediate metabolic condition between EU and HR (which is further supported by the intermediate levels of the thyroid hormones in our SHR group).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have recently shown that glucose uptake in muscle in HR is indeed resistant to insulin, but this defect is masked by a marked increase in blood flow (4); this could be attributed to the dramatic decrease in intracellular pathways of insulin-stimulated glucose metabolism (such as glycogen synthesis) (25,26). In addition, tumor necrosis factor a and interleukin 6 may contribute to insulin resistance in the metabolism of both lipids and glucose in HR (27). These findings support the results of the present study: in HR patients, glucose uptake in monocytes in the presence of insulin was significantly decreased compared to euthyroid subjects; the SHR group showed an intermediate response suggesting that SHR is an intermediate metabolic condition between EU and HR (which is further supported by the intermediate levels of the thyroid hormones in our SHR group).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, peripheral insulin resistance in hyperthyroidism may be explained by the increased secretion of bioactive mediators (adiponectins), such as interleukin-6 and TNF-alpha, by adipocytes. Higher levels of these adiponectins have been observed in women with hyperthyroidism [18].…”
Section: Hyperthyroidismmentioning
confidence: 97%
“…**P < 0.01 however, this finding remains controversial [27]. It is widely reported that IL-6 and tumor necrosis factor alfa (TNFα) are related to the development of insulin resistance in hyperthyroidism [28]. The roles of these 2 cytokines are important in the pathogenesis of insulin resistance.…”
Section: Fig 2 Serial Changes In Serum Il-18 Levels In Patients Withmentioning
confidence: 99%